Secretome of Hypoxia-Preconditioned Mesenchymal Stem Cells Ameliorates Hyperglycemia in Type 2 Diabetes Mellitus Rats - Widyaningsih, Wita; Putra, Agung; Priyantini, Sri; Muhar, Adi Muradi; Sumarawati, Titiek; Trisnadi, Setyo; Amalina, Nur Dina; Alif, Iffan; Prasetio, Ardi; Satria Irawan, Risky Chandra (Trends in Sciences, 2024)
Introduction: Type 2 diabetes mellitus (T2DM) is a prevalent form of diabetes that affects 90 - 95 % of all diabetic patients. Insulin sensitizers and insulin exogenous supply could temporarily ameliorate hyperglycaemia; however, they are accompanied by side effects. As a result, new approaches are required to address insulin resistance and regenerate beta cells simultaneously. The secretome of hypoxic mesenchymal stem cells (SH-MSCs) contains various growth factors and anti-inflammatory cytokines that could potentially enhance insulin resistance and improve pancreatic function. Objectives: In this study, we performed SH-MSCs infusion to ameliorate HFD-induced hyperglycaemia in T2DM rats. Methods: We created a T2DM rat model using a combination of a high-fat diet (HFD) and streptozotocin (STZ) administration. Then, we administered SH-MSCs injection at doses of 250 and 500 µL and assessed the therapeutic effects of SH-MSCs. We also investigated the potential underlying mechanisms involved. Results: The administration of SH-MSCs improved hyperglycemia in rats with T2DM. Infusion of SH-MSCs at 500 µL dose decreased homeostatic model assessment for insulin resistance (HOMA-IR). Histological analysis revealed that injection of SH-MSCs alleviated morphological damage of pancreas. SH-MSCs administration also inhibit the level of IL-6 and promote the expression of CD163 type 2 macrophage. Conclusion: The results of our study indicate that SH-MSCs have the potential to improve hyperglycemia and exert a protective effect on T2DM rats. HIGHLIGHTS Administration of SH-MSCs effectively improved hyperglycemia and decreased insulin resistance in TD2M rats through modulation of IL-6 levels and promotes the expression of CD163 type 2 macrophage Histological analysis demonstrated the protective effect of SH-MSCs on pancreatic morphology SH-MSCs hold promise for improving hyperglycemia, insulin resistance, and providing a protective effect in TD2M GRAPHICAL ABSTRACT